Effect of spinel and perovskite coatings on the long term oxidation of a ferritic stainless steel in H2/H2O atmosphere. (March 2019) - Ardigo-Besnard, M.R.; Popa, I.; Chevalier, S.
Graphical abstract: Highlights: The K41X alloy was surface-modified via the application of coatings. La0.8 Sr0.2 MnO3, LaNi0.6 Fe0.4 O3, Co2 MnO4 and Co3 O4 were chosen as coatings. Isothermal oxidation tests were performed up to 3000 h at 800 °C in H2 -H2 O. Fe-rich oxides growth was avoided and a protective (Cr, Mn)3 O4 /Cr2 O3 scale formed. All coatings were efficient in preventing from Cr evaporation up to 3000 h ageing. Abstract: In order to improve the oxidation behaviour of AISI441 ferritic stainless steel in H2 /H2 O atmosphere at 800 °C, four oxide coatings were tested: two perovskites (La0.8 Sr0.2 MnO3 and LaNi0.6 Fe0.4 O3 ) deposited by screen printing and two spinels (MnCo2 O4 and Co3 O4 ) obtained by PVD technique. Isothermal oxidation tests performed up to 3000 h showed that the coating presence avoided Fe oxides growth, which occurs for the raw alloy in the same conditions. Moreover, a protective (Cr, Mn)3 O4 /Cr2 O3 layer formed between the substrate and the coating. Any presence of Cr was not detected within the coatings, indicating that all compositions were efficient in preventing Cr evaporation.